Extreme Phenotypes With Identical Mutations: Two Patients With Same Non-sense NHEJ1 Homozygous Mutation - Recio, Maria J.; Dominguez-Pinilla, Nerea; Perrig, Melina Soledad; Rodriguez Vigil-Iturrate, Carmen; Salmón-Rodriguez, Nerea; Martinez Faci, Cristina; Castro-Panete, María J.; Blas-Espada, Javier; López-Nevado, Marta; Ruiz-Garcia, Raquel; Chaparro-García, Rebeca; Allende, Luis M.; et al. (Frontiers in Immunology, 2019)
Cernunnos/XLF deficiency is a rare primary immunodeficiency classified within the DNA repair defects. Patients present with severe growth retardation, microcephaly, lymphopenia and increased cellular sensitivity to ionizing radiation. Here, we describe two unrelated cases with the same nonsense mutation in the NHEJ1 gene showing significant differences in clinical presentation and immunological profile but a similar DNA repair defect.